Removal of Escherichia coli by Intermittent Operation of Saturated Sand Columns Supplemented with Hydrochar Derived from Sewage Sludge - Jae Wook Chung; Oghosa Charles Edewi; Jan Willem Foppen; Gabriel Gerner; Rolf Krebs; Piet Nicolaas Luc Lens (Applied Sciences, 2017)
Hydrothermal carbonization (HTC) technology can convert various types of waste biomass into a carbon-rich product referred to as hydrochar. In order to verify the potential of hydrochar produced from stabilized sewage sludge to be an adsorbent for bacterial pathogen removal in water treatment, the Escherichia coli’s removal efficiency was determined by using 10 cm sand columns loaded with 1.5% (w/w) hydrochar. Furthermore, the removal of E. coli based on intermittent operation in larger columns of 50 cm was measured for 30 days. Since the removal of E. coli was not sufficient when the sand columns were supplemented with raw hydrochar, an additional cold-alkali activation of the hydrochar using potassium hydroxide was applied. This enabled more than 90% of E. coli removal in both the 10 cm and 50 cm column experiments. The enhancement of the E. coli removal efficiency could be attributed to the more hydrophobic surface of the KOH pre-treated hydrochar. The idle time during the intermittent flushing experiments in the sand-only columns without the hydrochar supplement had a significant effect on the E. coli removal (p < 0.05), resulting in a removal efficiency of 55.2%. This research suggested the possible utilization of hydrochar produced from sewage sludge as an adsorbent in water treatment for the removal of bacterial contaminants.